DYSLEXIA AND SPELLING IN TWO DIFFERENT ORTHOGRAPHIES (GREEK VS. ENGLISH): A LINGUISTIC ANALYSIS. - Baseki, PhD, Julie; Andreou, PhD, Georgia; Tzivinikou, PhD, Sotiria (JOURNAL OF ADVANCES IN LINGUISTICS, 2016)
In our study spelling skills of 40 dyslexic (mean age 13,2 years) and 40 non dyslexic children (mean age 10,9 years) matched on the basis of their general level of language proficiency and foreign language acquisition, were assessed through a dictation passage spelling test and the composing of picture elicited narratives, in both Greek (L1) and English (L2). Results indicate that spelling performance is affected by the distinct nature of each orthographic system. In both groups, phonological errors were the least frequent type of spelling errors, while the predominance of morphological and etymological errors indicates both groups' persistent difficulties with applying linguistic rules and systematicities. As expected, dyslexics made more errors of all types despite the fact that the two groups' error profiles did not differ qualitatively. Finally, both groups‟ revising and pausing behaviour indicated that spelling has been the main concern for both dyslexic and non dyslexic writers and confirmed the dyslexics' deficient error detection mechanism.